2015
DOI: 10.1016/j.apcatb.2014.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of Cu/SAPO-34 catalysts for NH3-SCR 2: Solid-state ion exchange and one-pot synthesis

Abstract: Cu/SAPO-34 catalysts are synthesized using two methods: solid-state ion exchange (SSIE) and one-pot synthesis. SSIE is conducted by calcining SAPO-34/CuO mixtures at elevated temperatures. For the onepot synthesis method, Cu-containing chemicals (CuO and CuSO 4) are added during gel preparation. A high-temperature calcination step is also needed for this latter method. Catalysts are characterized with surface area/pore volume measurements, temperature programmed reduction (TPR), electron paramagnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(131 citation statements)
references
References 41 publications
5
124
0
Order By: Relevance
“…At lower Cu contents, they are positioned at sites in the 6-membered rings and at higher contents, also within the large cages [19]. There are indications that Cu ions may be sited similarly in Cu/SAPO-34 [11]. In addition to its importance for SCR activity, copper loading may also yield useful information on the reaction selectivities and pathways, as we have previously shown for Cu/Beta [16].…”
Section: Characterisation By X-ray Diffraction (Xrd)mentioning
confidence: 85%
See 2 more Smart Citations
“…At lower Cu contents, they are positioned at sites in the 6-membered rings and at higher contents, also within the large cages [19]. There are indications that Cu ions may be sited similarly in Cu/SAPO-34 [11]. In addition to its importance for SCR activity, copper loading may also yield useful information on the reaction selectivities and pathways, as we have previously shown for Cu/Beta [16].…”
Section: Characterisation By X-ray Diffraction (Xrd)mentioning
confidence: 85%
“…Thus, a number of studies have been published on Cu/SAPO-34 synthesised via one-pot synthesis or solid state ion exchange and on commercially-produced catalysts [11,12]. However, very few details are available as to the procedure of aqueous ion exchange for Cu/SAPO-34.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested clearly that appropriate calcination temperature was important for the catalytic activity of Cu-SAPO-34. Gao et al [13] studied solid-state reaction between SAPO-34 and CuO under different calcination temperatures and times and found that a portion of CuO ($67%) converted to isolated Cu 2+ ions after the SSIE treatment at 800°C for 16 h. It suggested that the copper species in Cu-SAPO-34 can be redistributed to yield an active catalyst upon high temperature treatment. However, copper species distribution of Cu 5 -SAPO-34-T samples did not change distinctly ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The aqueous solution ion exchange method involves a two-step exchange process, filtering, washing and calcining, greatly limiting its application [11,12]. The solid-state ion exchange (SSIE) method is carried out under rather harsh conditions (calcining at 800°C), leading to decomposition of the framework [13,14]. Recently, one-pot hydrothermal synthesis method used low-cost copper-tetraethylenepentamine (Cu-TEPA) as Cu source and template to prepare Cu-CHA directly which was much simpler to perform, and might be applicable at industrial scale [15].…”
Section: Introductionmentioning
confidence: 99%